Pengembangan U-SHIELD: Aplikasi Self-Defense Remaja Berbasis Strategi Komunikasi Asertif Pencegah Cyberbullying - Nur Fadhilah Umar; Muhammad Rafli; Nurpadhillah Junaid Dilah; Nindah Nurul Mentari (Indonesian Journal of Learning Education and Counseling, 2022)
This study aims to develop an application based on assertive communication skills as adolescent self-defense in preventing, dealing with, and overcoming cyberbullying with quality, namely meeting the criteria of material content validity, feasibility, accuracy, and usefulness. This research is a development research approach, namely; define, design, develop, and disseminate. The population in this study were teenagers with the status of Makassar City Middle School students, namely SMAN 1 Makassar, Makassar National Junior High School, and SMPN 8 Makassar in the 2021/2022 academic year for grades 1, 2, and 3 with a sample of 300 students. The sampling technique used was purposive sampling. Data collection techniques used adapted ways of coping questionnaire, response questionnaires in the form of needs analysis to design applications, and content and media expert validation questionnaires. The data obtained were analyzed using descriptive statistical analysis and interater agreement. The results obtained stated that: (1) The results of descriptive statistical tests found that adolescents' self-defense was high, especially in the problem solving aspect, but in dealing with adolescent stress on emotional problems, it was classified as moderate; (2) 98.2% of teenagers really need application development and see the importance of applications to overcome cyberbullying. (3) The U-shield application meets the criteria for the validity and content of the material through an expert test. So it can be concluded that teenagers need self-defense to prevent, overcome and be able to control the emotional effects of cyberbullying